Tingkat Pembukaan Kanopi Hutan Akibat Kegiatan Pemanenan pada Sistem Silvikultur Tebang Pilih Tanam Indonesia (Opened Forest Canopy Caused by Forest Exploitation Using Indonesian Selectice Cutting and Planting Silvicultural System): Wahyudi - Admin JHT (Jurnal Hutan Tropika, 2019)
ABSTRACTForest exploitation (harvesting) on the production forest management using silviculturalsystem of Indonesian Selectice Cutting and Planting (ISCP) has been conducted since1989. This research was aimed to analyze forest degradation in the form of opened forestcanopy that be caused by harvesting using ISCP system. The research was located at theworking areas of 2018 at PT Gunung Meranti forest concession. Research samplesnamely 30 trees, they were divided into 6 diameter classes i.e. 41 to 50 cm, 51 to 60 cm,61 to 70 cm, 71 to 80 cm, 81 to 90 cm dan 91 cm up. Each diameter classes wascompiled into 5 trees. Research result show the equation of opened forest canopy whichcaused degraded forest that be analyzed using tree diameter, i.e. Y=24,472+0,4428X (R2=67,45%).Keywords: degradation, diameter, harvesting, equation